The Use of Frequency Lowering Technology in the Treatment of Severe-to-Profound Hearing Loss: A Review of the Literature and Candidacy Considerations for Clinical Application - Glista, Danielle; Scollie, Susan (Seminars in Hearing, 2018)
This article provides a review of the current literature on the topic of frequency lowering hearing aid technology specific to the treatment of severe and profound levels of hearing impairment in child and adult listeners. Factors to consider when assessing listener candidacy for frequency lowering technology are discussed. These include factors related to audiometric assessment, the listener, the type of hearing aid technology, and the verification and validation procedures that can assist in determining candidacy for frequency lowering technology. An individualized candidacy assessment including the use of real-ear verification measures and carefully chosen validation tools are recommended for listeners requiring greater audibility of high-frequency sounds, when compared with amplification via conventional hearing aid technology.
Keywords: frequency lowering; hearing aids; high frequency; severe-to-profound hearing impairment